Foodborne Bacterial Pathogens - Doyle, Michael P;Ed (Food science and technology (Marcel Dekker, Inc.), 1989)
Bacteria are estimated to cause some 24 million cases of diarrheal disease annually in the US. These papers have wide importance providing background information and recent research findings and giving a comprehensive, current understanding of bacterial pathogens associated with foods and their role